Frequency and voltage-dependent electrical parameters, interface traps, and series resistance profile of Au/(NiS:PVP)/n-Si structures - Ulusoy, M.; Altındal, Ş.; Durmuş, P.; Özçelik, S.; Azizian-Kalandaragh, Y. (Journal of materials science. Materials in electronics, 2021)
A thin (NiS-doped PVP) interface layer was spin-coated on n-Si substrate, and between Au contact were prepared on the surface by the sputtering method and then their basic electrical features, for example, diffusion-potential (V D ), doping density of donor-atoms (N D ), Fermi-energy (E F ), barrier-height (Φ B ), and depletion layer-width (W D ) were extracted reverse-bias C −2 -V plots as function frequency and voltage. The voltage profile of interface/surface-states (N ss )/ relaxation-times (τ), and series resistance (R s ) were also obtained from the admittance and Nicollian-Brews method, respectively. Strongly frequency-dependent and voltage, especially in both accumulation and depletion regions due to the existence of N ss , R s, and polarization as well as (NiS-doped PVP) organic interlayer. At low frequency, the observed higher value of C and G shows that thin (NiS:PVP) interlayer can be successfully used to obtain high charges/energy storage (MPS) structure/capacitor instead of conventional insulator layer performed traditional methods. As a result, the observed important changes in electrical parameters with frequency and voltage depend on N ss , their τ, R s , organic interlayer and interfacial or dipole polarization.